Messaging with appeal to intrinsic or relational values shows potential to shift demand for wildlife as pets - Harry Marshall; Nigel J. Collar; Alexander C. Lees; Andrew Moss; Pramana Yuda; Stuart J. Marsden (People and Nature)
Abstract Overharvesting of wildlife for trade is a key driver of biodiversity loss. Messaging that is aligned with people's values could play a significant role in reducing this impact through behaviour change. Using an online survey, we sought to gauge the willingness among bird hobbyists, breeders, and song contestants to change their bird‐keeping behaviours, and to identify barriers to such change. We then evaluated the persuasiveness of various messages that potentially align with people's values (e.g. addressing conservation, cultural and health considerations), each framed as positive or negative, and with outcomes involving a move to commercially bred birds or cessation of purchasing wild‐caught birds. We identified a degree of plasticity in behaviour, with most respondents perceiving the keeping of wild‐caught birds to be a conservation problem, and a majority claiming they would attempt to breed birds in the future. However, while most respondents acknowledged the illegality of both buying and catching wild birds, they also recognised that most birds in markets are wild‐caught because they are easier and cheaper to source than captive‐bred birds. Messages about the damage done by over‐exploitation to wild bird populations, to the future of bird‐keeping itself, and about the benefits of keeping captive‐bred over wild‐caught birds, were most effective. Messages about generational, legal and especially health concerns appeared to gain little traction. The persuasiveness of these messages varied little across bird‐keeping groups, but age‐ and user‐groups differed in their most trusted sources of information and the media they consulted. Our results suggest that appealing to people's concern over the intrinsic value of wildlife or the relational value of cultural heritage might be more effective at shifting demand for wildlife products than more instrumental or utilitarian considerations. Effective messaging should focus on the negative impacts of over‐exploitation on Indonesia's wildlife and/or national heritage, and on the positive aspects of sustainable captive‐bred alternatives, and be transmitted via multiple media, including local and faith leaders (choice varying geographically), to maximise outreach to the diverse bird‐keeping community. Read the free Plain Language Summary for this article on the Journal blog.